Pedoman Tatalaksana Takiaritmia Supraventrikular (TaSuV) - Sunu Budhi Raharjo; Yoga Yuniadi; Muzakkir Muzakkir; Ignatius Yansen; Dian Andina Munawar; Dony Yugo Hermanto (Jurnal Kardiologi Indonesia, 2017)
No abstract